2010
DOI: 10.2215/cjn.04120609
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Rituximab in the Treatment of Recurrent Idiopathic Membranous Nephropathy after Kidney Transplantation

Abstract: Background and objectives: Recurrence of the original kidney disease after renal transplantation is an increasingly recognized cause of allograft loss. Idiopathic membranous nephropathy (iMN) is a common cause of proteinuria that may progress to ESRD. It is known that iMN may recur after kidney transplantation, causing proteinuria, allograft dysfunction, and allograft loss. Limited data regarding the frequency and treatment of recurrent iMN are available.Design, setting, participants, & measurements: In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
73
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 23 publications
3
73
0
7
Order By: Relevance
“…The reason is not clear, but may be associated with donorspecific antibodies (HLA or non-HLA). As with native IMN, some success has been claimed for rituximab in small series, 31 but the numbers are small and RCTs are needed before this agent moves into routine use.…”
Section: Discussionmentioning
confidence: 99%
“…The reason is not clear, but may be associated with donorspecific antibodies (HLA or non-HLA). As with native IMN, some success has been claimed for rituximab in small series, 31 but the numbers are small and RCTs are needed before this agent moves into routine use.…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab, a chimeric anti-CD20 monoclonal antibody used for anti-B cell therapy, has recently been investigated as a promis-ing agent for the treatment of membranous nephropathy (MN) in the native kidney and for recurrent MN in the allograft. [2][3][4][5][6][7] Treatment response has been assessed by the attainment of a complete or partial clinical remission, whereas other laboratory parameters have not been useful in monitoring therapy.…”
mentioning
confidence: 99%
“…This finding differs from other studies that showed recurrence rates of 10% to 45%. 31 Other studies by Debiec and associates and Kennedy and associates demonstrated recurrence rates of 30% to 45%. 32,33 The difference between these results could be attributed to racial differences and the use of kidney grafts from deceased donors.…”
Section: Discussionmentioning
confidence: 92%